Environmental sustainability of run of the river hydropower projects: A study from western Himalayan region of India. (August 2016) - Kumar, Deepak; Katoch, S.S.
Abstract: Run of the river (RoR) hydropower projects are generally considered more environmentally sustainable as compared to their reservoir based counterparts. Further, impacts of these projects are supposed to be in proportion to their installed capacity. Large numbers of this category of hydropower projects in different size ranges are coming up in Himalayan regions. Un-sustainable construction/operation practices adopted during development and/or running of these projects are posing an environmental threat to this fragile and youngest mountain range of the world. This research paper presents a public perception cum data collection study on the environmental impacts of small and large RoR hydropower projects located in western Himalayan region of India. A structured questionnaire was designed to collect the primary data pertaining to intangible impacts while secondary data was collected to analyse tangible environmental parameters. The study concludes that every environmental impact of SHPs is not 'small' as compared to LHPs. Ignoring the environmental impacts of SHPs may not be a good practice. Highlights: RoR projects require to be investigated for their environmental sustainability. Environmental impacts of SHPs are not worth ignoring. Environmental impacts of RoR projects are not proportional to the project size.